Representations of public health professionals on integration and complementary practices in Viçosa-MG, Brazil (Research, Society and Development, 2021)
The present study aims to analyze the representations of public health professionals of the municipality of Viçosa - MG on Integrative and Complementary Practices (referred in this article as PICs). The methodology applied in this research is qualitative. Based on the history of the political institutionalization of these practices, the Theory of Social Representations is used to analyze the interviews. The results are organized in two thematic axes, which deal with the knowledge and acceptance of the integrative practices and the insertion of the healers in the Health Unic System (referred in this article as SUS). It is observed that the professionals are not aware of the National Policy of Integrative and Complementary Practices, but recognize the practices covered by it. It is concluded that the inefficiency in the disclosure of the policy has influences in the perceptions about its effectiveness and possibility of being executed.